Planning for Passenger Movement Flow Systems at Terminal 1 Juanda Airport Due to Health Protocol Implementation - Evangelista; Ahyudanari, Ervina (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
The passenger terminal is one of the most important aspects of the airport system because, in general, the terminal is the main link for passenger access to air transportation modes, namely airplanes. Many activities and processes are related to air travel at the terminal, from purchasing tickets on departure to baggage claim on arrival. As recorded on the online website of the Central Statistics Agency, the number of passengers at Juanda Airport has decreased significantly during the COVID-19 pandemic. Therefore, COVID-19 appeared at the end of 2019 and greatly affected operational activities in the terminal, especially at Terminal 1 Juanda Airport. This study analyzed the number of peak hour passengers after New Normal, changes in passenger movements after the implementation of the health protocol, namely the existence of COVID-19 free test facilities in the airport area, validation of COVID-19 free tests, the use of HAC, and analyzes the adequacy of existing facilities and area at T1 Juanda. It was to find out the number of passengers during peak hours that can still be accommodated while implementing health protocols, namely social distancing. In addition, to find ways to deal with the accumulation of passengers at specific points in the terminal. Based on the calculation results in this study, it was found that the number of passengers during this pandemic decreased by 228%, with the number of passengers during peak departure hours of 1607 passengers and passengers during peak arrival hours of 1991 passengers. Furthermore, to overcome the new queue points that appear in the Terminal 1 Juanda Airport area, it is planned to add deks and/or validation officers in the COVID-19 free test letter validation area located in the arrival’s hall and the HAC validation area located in the baggage claim is doubled, namely 10 tables and 8 tables respectively. In addition, it is also planned to replace the x-ray device with an Automated Tray Return System system to overcome the buildup of passengers in the security checkpoint 1 area.